1983
DOI: 10.1159/000457311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aminophylline on Brain Blood Flow in the Newborn Piglet

Abstract: The effect of 6 mg/kg of aminophylline on brain blood flow was examined in newborn piglets. Arterial plasma aminophylline concentration averaged 7 mg/1. Total brain, regional brain (cerebrum, cerebellum and stem) and eye blood flow as well as the total brain oxygen consumption were not altered by aminophylline treatment. Choroid plexus blood flow was five times higher than the total brain blood flow in these newborn piglets. In contrast to brain blood flow, choroid plexus blood flow decreased significantly fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…These findings agree with those from a comparable study in piglets given 6 mg/kg theophylline ethylenediamine (25) and argue against a direct cerebral vascular or metabolic effect of theophylline at this dose.…”
Section: Discussionsupporting
confidence: 90%
“…These findings agree with those from a comparable study in piglets given 6 mg/kg theophylline ethylenediamine (25) and argue against a direct cerebral vascular or metabolic effect of theophylline at this dose.…”
Section: Discussionsupporting
confidence: 90%
“…The constancy of the angle of insonation is not easily achieved with this method. On the contrary, using the newborn piglet un der conditions of controlled ventilation to maintain a constant Pco2> Stonestreet et al [5] showed that a therapeutic dose of ami nophylline (6 mg/kg) did not alter CBF. McPhee and Maxwell [8] confirmed these findings with theophylline (10 mg/kg) in the same animal model.…”
Section: Discussionmentioning
confidence: 98%
“…If renal, cardiovascular and gastrointesti nal side effects of these drugs are well docu mented [2,3], few studies have examined the effects of aminophylline on the developing brain [4,5], However, there is some evidence that, in adults, aminophylline and caffeine reduce cerebral blood flow (CBF). CBF was measured with either the xenon-133 inhala tion technique, or the xenon-133 intracarot id injection method [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hypocapnia has been recorded after methylxanthine administra tion in both preterm neonates [60,66] and in adult animals [28-32] and humans [35]. The decrease in CBF can be avoided and thus methylxanthine safely used in the treatment of apnea of prematurity when pCCF is moni tored and maintained at a constant level [67],…”
Section: Effects O F M Ethylxanthines On Cerebral Blood Flow and Metamentioning
confidence: 99%